f(x+y)=f(x)+f(y) , f(1)=3 , f(x)=? pls explain !!
- print Print
- list Cite
Expert Answers
briefcaseTeacher (K-12)
calendarEducator since 2011
write3,149 answers
starTop subjects are Math, Science, and Business
We are given that f(x+y)=f(x)+f(y) and that f(1)=3.
We assume that f(x) is continuous. (A non-continuous image is possible, but requires real analysis which is beyond a high school class.)
Then f is of the form f(x)=kx (or y=kx) for some `kinRR` .(f(0+0)=f(0)+f(0)==>f(0)=2f(0) so f(0)=0. Also f(rx)=f(x)+f(x)+ ... +f(x) (r times)==>f(rx)=rf(x).
So plugging in the known values we get `3=k*1 ==>k=3`
----------------------------------------------------------------
The solution is f(x)=3x
----------------------------------------------------------------
Checking: f(1+3)=f(4)=12=3+9=f(1)+f(3) as required.
Related Questions
- f(x) = (x-3)/(x+1) find f'(0)f(x) = (x-3)/(x+1) find f'(0)
- 2 Educator Answers
- Determine f(x) if 2*f(x) + 3*f(1-x) = 4x - 1
- 1 Educator Answer
- Given f(x) and g(x), please find (fog)(X) and (gof)(x) f(x) = 2x g(x) = x+3
- 1 Educator Answer
- if f(x)=2x-3 and fg(x)=2x+1,find g(x)
- 1 Educator Answer
- `f'''(x) = cos(x), f(0) = 1, f'(0) = 2, f''(0) = 3` Find `f`.
- 1 Educator Answer
calendarEducator since 2011
write5,348 answers
starTop subjects are Math, Science, and Business
The problem provides the information that `f(1) = 3` , hence, putting `x = 1,y = 0` and f(y) = 0 yields:
`f(1+0) = f(1) + f(0) =gt f(1) = 3`
Putting `x = y` yields:
`f(x + x) = f(x) + f(x) =gt f(2x) = 2f(x)`
Putting `x=y=1` yields:
`f(1+1) = f(1)+f(1) =gt f(2) = 2f(1) =gt f(2) = 2*3 = 6`
Putting `x = 2, y=1` yields:
`f(2+1) = f(2) + f(1) =gt f(3) = 6 + 3 = 9`
`f(k+1) = f(k) + 3 =gt f(k) = f(k+1)-3`
Hence, evaluating f(x), considering different values for y, yields: for `y = 0, x=1=gt f(1)=3` , for `x=y =gt f(x) = f(2x)/2` ; for `y =1` and `x =1,2,...,x` , then `f(x) = f(x+1)-3` .